CARDIAC SURGERYDifferent techniques for aortic valve repair and the associated root reconstruction – prospective long-term follow-up of the first 100 patients - Jasinski, Marek J.; Gocol, Radosław; Malinowski, Marcin; Hudziak, Damian; Duraj, Piotr; Frackiewicz, Joanna; Kargul, Tomasz; Deja, Marek; Woś, Stanisław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Aim: The advantages of aortic valve and aortic root reconstructive surgery include the provision of natural postoperative valve hemodynamics and the avoidance of prosthetic valve-related complications. A systematic approach based on functional classification of aortic regurgitation allows standardization and reproducibility. Its potential applicability, however, is limited by the relative lack of long-term follow-up data. Material and methods : Between the years 2003 and 2013, 225 consecutive patients (175 male, 50 female, mean age 51.3 years) with severe aortic regurgitation and aortic root enlargement underwent aortic valve repair or sparing surgery. The first 100 patients operated on during the first 5 years were prospectively enrolled in the study in order to achieve a 105-month follow-up. They underwent aortic valve repair and associated aortic root reconstruction. This prospective study is aimed at assessing the major endpoints of overall survival and freedom from reoperation. Additionally, log-rank testing for the risk factors associated with overall mortality, reoperation, and aortic valve repair failure was performed. Results: Among 225 patients, early mortality occurred in the case of 5 patients (2.2%), while 6 (2.5%) patients experienced early valve failure. In a prospective analysis performed on the first 100 patients, long-term results achieved with Kaplan-Meier analysis showed a survival rate of 93% and freedom from reoperation at the level of 91.3%. The risk factors for overall mortality included NYHA class, creatinine level, and perioperative root replacement as reimplantation. Redo operation was associated with bicuspid aortic valve and perioperative leaflet resection with pericardial patch repair. Conclusions: Eighty-eight-month follow-up data from this prospectively analyzed cohort of patients prove that aortic valve repair associated with aortic root reconstruction can be performed with satisfactory results.